2004
DOI: 10.1111/j.1365-2958.2004.04285.x
|View full text |Cite
|
Sign up to set email alerts
|

HopPtoN is a Pseudomonas syringae Hrp (type III secretion system) cysteine protease effector that suppresses pathogen‐induced necrosis associated with both compatible and incompatible plant interactions

Abstract: SummaryPseudomonas syringae pv. tomato DC3000 causes bacterial speck disease in tomato, and it elicits the hypersensitive response (HR) in non-host plants such as Nicotiana tabacum and Nicotiana benthamiana . The compatible and incompatible interactions of DC3000 with tomato and Nicotiana spp ., respectively, result in plant cell death, but the HR cell death occurs more rapidly and is associated with effective plant defense. Both interactions require the Hrp (HR and pathogenicity) type III secretion system (TT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
96
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(99 citation statements)
references
References 51 publications
2
96
0
1
Order By: Relevance
“…Interestingly, even though GRS447 does not induce a wilting phenotype on Arabidopsis, this mutant can colonize the plant similarly to the wild-type strain, indicating that symptoms and bacterial internal growth could be dissociated. This observation has already been reported to be the case for two P. syringae T3SS effectors (43,44). For R. solanaceraum, development of wilt symptoms is directly associated with the obstruction of the xylem vessels by the exopolysaccharides (EPS) produced by the bacteria.…”
Section: Discussionmentioning
confidence: 79%
“…Interestingly, even though GRS447 does not induce a wilting phenotype on Arabidopsis, this mutant can colonize the plant similarly to the wild-type strain, indicating that symptoms and bacterial internal growth could be dissociated. This observation has already been reported to be the case for two P. syringae T3SS effectors (43,44). For R. solanaceraum, development of wilt symptoms is directly associated with the obstruction of the xylem vessels by the exopolysaccharides (EPS) produced by the bacteria.…”
Section: Discussionmentioning
confidence: 79%
“…HopAA1-1 elicits cell death when expressed in yeast and plant cells (25). HopN1 is a cysteine protease that can suppress ETI-associated cell death (27). How these few T3Es function together to form a minimal repertoire may be complex, because T3Es can have multiple domains and interfering activities.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms by which HopN1 suppresses symptom production were not investigated. However, it was shown that HopN1 has Cys protease activity in vitro characteristic of papain-like enzymes, suggesting that it might cleave specific host targets associated with defense (Ló pez- Solanilla et al, 2004).…”
Section: Discussionmentioning
confidence: 99%